Plasmapheresis for the Treatment of Anti-M Alloimmunization in Pregnancy - Yohei Maki; Junko Ushijima; Seishi Furukawa; Hiroko Inagaki; Hiroyuki Takenouchi; Shouichi Fujimoto; Hiroshi Sameshima (Case Reports in Obstetrics and Gynecology)
Intrauterine transfusion is the standard antenatal treatment for a fetus with severe anemia. Plasmapheresis is an alternative treatment for cases with a history of severe hemolytic disease of the fetus and newborns at less than 20 weeks of gestation. There is only one previous report of plasmapheresis for the anti-M alloimmunization in pregnancy, and we report here on the successful treatment of plasmapheresis for anti-M alloimmunization. A woman with a history of intrauterine fetal death at 24 weeks of gestation due to severe fetal anemia caused by anti-M alloimmunization received plasmapheresis once or twice a week from 14 weeks of gestation onward. An intrauterine blood transfusion was conducted at 28 weeks, and a cesarean section was performed at 31 weeks. The infant had anemia and jaundice but was discharged at day 46. Plasmapheresis may delay the development of fetal anemia and reduce the risk of early and repeat intrauterine transfusion in cases of anti-M alloimmunization in pregnancy.